Interaction of tin-chloride complexes of palladium with silica gels, which contain sulfur-containing functional groups - Лещенко, В.; Циганович, O.; Трохимчук, A. (Київський національний університет імені Тараса Шевченка, 2007)
The sorption of Pd (II) tin-chloride complexes on silica gel impregnated by polyhexamethyleneguanidine and following synthesis of sorbents' on its basis containing complexing functional groups with sulfur is researched. It is shown, that the palladium quantitative extraction on the given sorbents from 1–4 M HCl solutions is possible.

Досліджено сорбцію оловохлоридних комплексів Pd(II) на сілікагелі імпрегнованому полігексаметиленгуанідином та подальшим синтезом на його основі сорбентів, які містять комплексоутворювальні сірковмісні функціональні групи. Показано, що на даних сорбентах можливе кількісне вилучення паладію з розчинів 1–4 М HCl.
Взаємодія оловохлоридних комплексів паладію з силікагелями, що містять сірковмісні функціональні групи
Keywords: -; -; -; -